Translational Oral Health Research (Springer International Publishing, 2018)
This book is the first to be devoted to translational research - which aims to expedite the transfer of knowledge gained in the lab to clinical practice - within the field of oral health. It is examined how basic sciences and basic research are providing new methods and materials that will enable clinicians to treat patients more effectively. Readers will gain a translational perspective on a variety of oral conditions and related systemic diseases. Individual chapters are devoted to such topics as dental biomaterials, implants, and tissue engineering. The importance of evidence-based research and the roles and comparative value of preclinical and clinical trials are also highlighted. Knowledge of translational and clinical research is essential in understanding how new inventions and developments are being accomplished, and what regulations and guidelines need to be taken into account when planning studies, and not forgetting the ethical aspects of any research. Translational Oral Health Research is the first book to be devoted entirely to the subject, and it will be of interest to both researchers and practitioners.